Growth of Ga2O3 film on ScAlMgO4 substrate by mist-chemical vapor deposition. (1st June 2023) - Yamashita, Syuhei; Moriya, Ryo; Takane, Hitoshi; Wada, Yuuichi; Yamafuji, Yuto; Kikawa, Junjiroh; Matsukura, Makoto; Kojima, Takahiro; Shinohe, Takashi; Kaneko, Kentaro; Araki, Tsutomu
Abstract: ScAlMgO4 (SAM) substrates have a trigonal structure with high cleavability in the c-plane. Because this substrate can be easily cleaved, gallium oxide (Ga2 O3 ) can be grown on the SAM substrate, and the difficulty in the heat dissipation of Ga2 O3 may be solved. Therefore, in this study, we performed Ga2 O3 growth on a SAM substrate using mist-chemical vapor deposition. When the growth temperature was varied at 500 °C, 600 °C, and 700 °C, ε -Ga2 O3 (004) grew dominantly, and the crystallinity improved with increasing temperature. Moreover, the grown ε -Ga2 O3 had orthorhombic structure and formed rotational domains. Furthermore, a phase transition to β -Ga2 O3 was achieved by annealing the resulting ε -Ga2 O3 on the SAM substrates. We also succeeded in separating the SAM substrates on which the Ga2 O3 thin films were grown.